Examining the association between government-sponsored product ratings and firm political participation. Issue 2 (15th May 2017) - Cavazos, David E.; Rutherford, Matthew
Abstract : Purpose: The purpose of this paper is to apply firm aspiration theory to explore how firms respond to government product ratings. Design/methodology/approach: Longitudinal examination of nine automobile manufacturers during National Highway Traffic and Safety Administration crash tests in the USA. Findings: Firms take specific external actions to influence the political mechanisms that support ranking schemes when product ratings are below those of rivals and when previously highly rated products decline. In addition, firms receiving rankings above those of their competitors are found to be less likely to take such action, even when their overall ratings declined. Similarly, firms seeing improvements in previously low-rated products will take fewer actions aimed at influencing the political mechanisms that support rating schemes. Originality/value: The primary contribution of this research is in establishing when firm product ratings will result in actions to influence external ratings criteria. Previous research has shown that firms respond to organizational ratings by taking action aimed at improving subsequent performance. The current research builds on such work by applying aspiration theory in an effort to predict and explain when and why certain ratings will attract firm attention to the external mechanisms that support such ratings.